Livestock and Climate Household Survey in Kenya and Ethiopia - Gichuki, Leah; Worku, Tigist; Njamba, Harrison; Getahun, Elizabeth; Kiptoo, Emmaculate; Habermann, Birgit (International Livestock Research Institute, 2023)
This is training manual to guide field enumerators and supervisors in understanding the survey questionnaire and logistical planning.